2020
DOI: 10.2174/0929867325666180831151055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-clay Nanocomposites as Carriers for Controlled Release

Abstract: The present review aims to summarize the research efforts undertaken in the last few years in the development and testing of hydrogel-clay nanocomposites proposed as carriers for controlled release of diverse drugs. Their advantages, disadvantages and different compositions of polymers/biopolymers with diverse types of clays, as well as their interactions are discussed. Illustrative examples of studies regarding hydrogel-clay nanocomposites are detailed in order to underline the progressive researches on hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 201 publications
1
16
0
Order By: Relevance
“…The change of the clay basal spacing (d 001 ) indicates the structure of GelMA-clay nanocomposites. Therefore, intercalation and/or exfoliation of composites was achieved as a consequence of GelMA insertion between silicate nanolayers [44,66]. The XRD profiles of all resulting nanocomposite samples indicated a decrease in 2θ values and, consequently, an increase in the d-spacing.…”
Section: Xrd and Tem Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…The change of the clay basal spacing (d 001 ) indicates the structure of GelMA-clay nanocomposites. Therefore, intercalation and/or exfoliation of composites was achieved as a consequence of GelMA insertion between silicate nanolayers [44,66]. The XRD profiles of all resulting nanocomposite samples indicated a decrease in 2θ values and, consequently, an increase in the d-spacing.…”
Section: Xrd and Tem Analysesmentioning
confidence: 98%
“…Several studies demonstrated that an intercalated or exfoliated state of clay generates different rheological behaviors of nanocomposite formulations. Conversely, the dispersion state of clay layers in polymers can be evaluated by analyzing the viscosity and the shear thinning exponent [44]. All synthesized inks exhibited shear thinning behavior with increasing shear rate ( Figure 6).…”
Section: Rheological and Mechanical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the compounding route, nanoclays were widely used for the development of injectable biomaterials, among different inorganic fillers [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These hydrophilic, layered silicates have the advantages of high surface area, tailorable surface chemistry and good biocompatibility [ 22 , 23 , 24 ]. Moreover, their outstanding ability to modulate flow properties, combined with their remarkable capacity to stabilize suspensions and emulsions, are excellent features of interest in the design and development of 3D-printing nanomaterials [ 19 , 20 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that nano clay particles have important values in regenerative medicine, with respect to cell adhesion and diffusion, and controlled drug release [ 160 ]. Clay has been proved to be an excellent filler and can be designed as a new hydrogel for 3D bioprinting.…”
Section: Nanometer Materials For Organ 3d Printingmentioning
confidence: 99%